“Scientific Collaborations” at the Level of Countries – A Case Study: A “Hard” Physical Geography and a “Soft” Economics Science Field - Zsófia Viktória Vida (DETUROPE)
Scientific collaboration is a widely studied science field in the recent decades. For measuring, it a tighter approach co-authorship is frequently used. Co-authorship base level is the level of articles and the co-authorship networks are based on articles and authors. In this study a rather different level was examined: the level of journals. We used the approach of collaboration analysis regarding the relation between countries and journals. Two main groups of methods were used: statistical analysis and networks analysis. The goal was to explore patterns between journals and countries. We investigated the relations between journal ranking and affiliated countries. We were interested if there are any differences between a “hard” and a “soft” science field. Both of our methodological approaches showed similar answers to research questions. The differences were minimal between “hard” and “soft” science fields. The journals with the highest and the lowest journal ranking had the highest inequalities in the distribution of countries.